2022
DOI: 10.1186/s12903-022-02179-1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of three-dimensional facial changes after surgically assisted rapid maxillary expansion (SARME): an observational study

Abstract: Background The abnormal facial features in maxillary transverse deficiency (MTD) are minimal and limited to a deficiency of the middle facial third, narrow nares and nasal base, and deepened nasolabial folds. The surgical expansion of the narrow maxilla has most obvious effects on widening of the maxillary dental arch and expansion of the maxillary and palatal structures in the transverse plane, however sagittal changes also occurs. The purpose of this observational study was to evaluate the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 26 publications
0
19
0
3
Order By: Relevance
“…The abnormal facial features of transversal maxillary deficiency include a deficiency of the mid-face and deepened nasolabial folds ( 21 ). Also, the effects of maxillary expansion were limited not only to the maxilla but also to the surrounding facial region.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal facial features of transversal maxillary deficiency include a deficiency of the mid-face and deepened nasolabial folds ( 21 ). Also, the effects of maxillary expansion were limited not only to the maxilla but also to the surrounding facial region.…”
Section: Discussionmentioning
confidence: 99%
“…Facial scanning methods can be used to assess facial changes obtained by a specific treatment, such as maxillofacial surgery or removable prostheses. [28][29][30][31] The described technique might not be able to accurately reproduce profile changes that a prosthodontic treatment can achieve. Artificial intelligence (AI) models have been described for predicting facial changes in patients with removable dentures.…”
Section: Discussionmentioning
confidence: 99%
“…Facial scanning methods capture the 3D surface of the patient's face. Facial scanning methods can be used to assess facial changes obtained by a specific treatment, such as maxillofacial surgery or removable prostheses 28–31 . The described technique might not be able to accurately reproduce profile changes that a prosthodontic treatment can achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using different methods (Betts et al, 1995;Betts & Lisenby, 1994;Garib et al, 2006) have confirmed that the effects of SARME are not seen only on the maxillary arch (Haas, 1961), and that dental changes (Starnbach et al, 1966) may also be expected. Facial soft tissue also changes after maxillary expansion, such as widening of the nose and increased projection in the cheek (Zupan et al, 2022). Zupan et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Facial soft tissue also changes after maxillary expansion, such as widening of the nose and increased projection in the cheek (Zupan et al, 2022). Zupan et al (2022). An evaluation of three-dimensional facial changes after surgically assisted rapid maxillary expansion (SARME): an observational study.…”
Section: Introductionmentioning
confidence: 99%